Occupational exposures, complementarity and the potential consequences of A.I. for the labour market: Some evidence from Ireland - Harry Williamson; Dermot Coates; Kevin Daly; Keith FitzGerald; Neil Gannon (Journal for Labour Market Research, 2025)
The adoption of AI technology by industry could significantly disrupt our current understanding of "typical" economic activity. As AI comes to pervade more sectors and occupations over time, it is likely that this technology will give rise to challenges and risks but also opportunities and benefits. There is, however, a significant degree of uncertainty regarding how future waves of technological change will impact the economy, including the labour market. Recent research has found that 40% of employment globally is exposed to AI and that this rises to 60% of employment in advanced economies. We analyse exposure and complementarity in tandem in order to better understand the potential impact across occupation types in Ireland. We find that Ireland is relatively more exposed to AI than is the case for other advanced economies. We also find find that female workers in Ireland are more likely to work in highly exposed roles compared to males, that younger Irish workers are more exposed to AI than are older workers, and that both exposure complementarity to AI increase in line with educational attainment. Finally, we contend that the extent to which AI augments, or replaces, human labour in the medium to long-run will depend on a variety of economic, social and policy factors, including levels of AI regulation.
Keywords: J21; J24; O31; 330; Artificial intelligence; Ireland; Labour markets; Technological change